Tails stabilize landing of gliding geckos crashing head-first into tree trunks - Robert Siddall (Nature Portfolio, 2021)
Siddall, Byrnes, Full, and Jusufi observe the function of the Asian flat-tailed gecko tail in gliding and landing on tree trunks in the field, complemented with mathematical and robotic models made of soft active materials. Altogether, their models show how geckos use an active tail reflex to brace the impact and reduce the risk of falling from landings on tree trunks.